Cationic polymerization of epoxides using novel xanthenyl phosphonium salts as thermo-latent initiator - Gupta, Mukesh Kumar; Singh, Raj Pal (Polymer Bulletin, 2008)
The present article describes the effect of steric and electronic factors on the efficiency of initiators based on novel xanthenyl phosphonium salts for cationic polymerization of epoxide monomers. 2-substituted (I(H), I(Cl), I(Me), and I(OMe)) xanthenyl phosphonium hexafluoroantimonate were synthesized and characterized by NMR ((1)H, (13)C and (31)P) and IR spectroscopy. The order of initiator activity in polymerization of glycidyl phenyl ether (GPE), was found as I(H)> I(Cl)> I(Me)> I(OMe). To understand the effect of steric factor, the polymerization of cyclohexene oxide (CHO) was performed and the order of activity was found as I(Cl)> I(H)> I(Me) > I(OMe). All the initiators were found to be latent at ambient temperature and initiates polymerization on thermal initiation. The order of initiator activity was influenced by electronic and steric factors in the system. The thermal stability of these salts was measured by Thermo gravimetric analysis (TGA). The solubility of the initiators in various organic solvents and epoxy monomers is also discussed.

Cell proliferation and controlled drug release studies of nanohybrids based on chitosan-g-lactic acid and montmorillonite - Depan, Dilip; Kumar, Annamalai Pratheep; Singh, Raj Pal (Acta Biomaterialia, 2009)
The present paper reveals the potential uses of novel hybrids of chitosan-g-lactic acid and sodium montmorillonite (MMT) in controlled drug delivery and tissue engineering applications. The drug-loaded novel nanohybrid films and porous scaffolds have been prepared by solvent casting and freeze-drying of the grafted polymer solution, respectively. Sodium Ibuprofen was loaded into nanohybrids of chitosan-g-lactic acid/sodium montmorillonite (CS-g-LA/MMT). Grafting of lactic acid and the drug loading were characterized by Fourier transform infrared spectroscopy. Formation of intercalated nanocomposites was confirmed by X-ray diffraction. Mechanical properties measurements have shown improvement in modulus and strength with expense of elongation by MMT reinforcement. The nanohybrids were found to be stable regardless of pH of the medium. The cell proliferation profile also shows that prepared nanohybrids are biocompatible. MMT reinforcement was found to control the drug (Ibuprofen) release rate in phosphate buffer saline solution (pH 7.4). MMT clay is therefore a viable additive for formulating sustained drug delivery systems based on lactic acid grafted chitosan. (C) 2008 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: Chitosan; clay; Controlled release; drug delivery systems; Nanocomposites

Chitosan and chitosan-co-poly(epsilon-caprolactone) grafted multiwalled carbon nanotube transducers for vapor sensing - Rana, Vijay Kumar; Akhtar, Shamim; Chatterjee, Sudipta; Mishra, Satyendra; Singh, Raj Pal; Ha, Chang-Sik (Journal of Nanoscience and Nanotechnology, 2014)
Vapor sensitive transducer films consisting of chitosan grafted (CNT-CS) and chitosan-co-polycaprolactone grafted (CNT-CS-PCL) multiwalled carbon nanotubes were prepared using a spray layer-by-layer technique. The synthesized materials (CNT-CS and CNT-CS-PCL) were characterized by Fourier transform infrared spectroscopy, C-13 CP/MAS solid state nuclear magnetic resonance spectroscopy and thermogravimetric analysis. Both CNT-CS and CNT-CS-PCL transducers were analyzed for the response of volatile organic compounds and toluene vapors. The ranking of the relative resistance (A(r)) for both chitosan based transducers were as follows: toluene < chloroform < ethanol < methanol. The CNT transducer (CNT-CS) was correlated selectively with an exponential law to the inverse of Flory-Huggins interaction parameters, chi(12). Dosing the films on the interdigitated electrodes with methanol, ethanol, chloroform and toluene vapors increased the film resistance of CNT-CS but decreased the resistance of CNT-CS-PCL compared to that of the reported transducers.
Keywords: Biocompatibility; Chitosan; MWCNTs; Poly(epsilon-caprolactone); Vapour Sensing

Chitosan-based bionanocomposites for biomedical application - Kumari, Sangeeta; Singh, Raj Pal; Chavan, Nayaku N.; Annamalai, Pratheep K. (Bioinspired Biomimetic and Nanobiomaterials, 2018)
Natural polymers have greatly impacted the advancement of modern medicine. Natural polymer-based biomaterials are biodegradable. A significant advantage of natural polymers is that they can be broken down and removed from the body after they have served their function. A wide range of novel biomaterials from natural polymers has been investigated to meet new challenges in medical science. Chitosan is one of the natural polymers which have been widely used in the biomedical field. Nanotechnology is one of the most popular areas of current research. In the area of nanotechnology, polymer and metal/metal oxide nanoparticle matrix-based nanocomposites have generated a significant amount of attention in the recent literature. These bionanocomposites have wide-ranging applications in drug delivery and tissue engineering. This paper discusses polymer-metal/metal oxide nanoparticle matrix-based nanocomposite biomaterials and their applications in the biomedical field - that is, drug delivery and tissue engineering applications.

Characterization of a novel nanocomposite film based on functionalized chitosan-Pt-Fe3O4 hybrid nanoparticles - Kumari, Sangeeta; Singh, Raj Pal; Chavan, Nayaku N.; Sahi, Shivendra V.; Sharma, Nilesh (Nanomaterials, 2021)
The development of organic-inorganic hybrids or nanocomposite films is increasingly becoming attractive in light of their emerging applications. This research focuses on the formation of a unique nanocomposite film with enhanced elasticity suitable for many biomedical applications. The physical property measurement system and transmission electron microscopy were used to analyze Pt-Fe3O4 hybrid nanoparticles. These nanohybrids exhibited magnetic effects. They were further exploited to prepare the nanocomposite films in conjunction with a chitosan-g-glycolic acid organic fraction. The nanocomposite films were then examined using standard techniques: thermogravimetric analysis, X-ray diffraction, Fourier transform infrared spectroscopy, and atomic force microscopy. Tensile strength testing demonstrated a significantly greater elastic strength of these nanocomposite films than pure chitosan films. The water absorption behavior of the nanocomposites was evaluated by measuring swelling degree. These nanocomposites were observed to have substantially improved physical properties. Such novel nanocomposites can be extended to various biomedical applications, which include drug delivery and tissue engineering.
Keywords: Chitosan; nanocomposite films; Pt-Fe3O4 hybrid nanoparticles; tensile strength testing; Thermogravimetric analysis